(untitled) (Journal of Student Affairs in Africa, 2026)
Owing to the history of South Africa, the challenges associated with new students entering institutions of higher learning each year are well established in the academic discourse and civil society circles. The quality of mathematics education is a particular cause for concern. South Africa, considered as a developing country, requires a student population with skills relevant to Science, Technology, Engineering, and Mathematics (STEM). In this article, we draw from personal experience by challenging the implicit assumption that ‘at risk’ students fall in line and seek available support for their benefit. Based on personal experience, we argue that students do not arrive at university tabula rasa; they draw on their worldviews and personal experiences as frames of reference. Therefore, they sometimes reject what they perceive as ‘intruding’ university interventions. It is to address this challenge that student advisors and all other stakeholders dedicated to student support must find creative and innovative approaches. Drawing on the Dunning-Kruger effect, we demonstrate that, at times, students suffer from inflated self-images. This is a metacognitive deficit that accounts for inflated self-appraisals and, as such, necessitates the interchangeable use of prescriptive and developmental advising.